The Management of Diabetes with Hyperuricemia: Can We Hit Two Birds with One Stone? - Wang Y; Lu J (Dove Medical Press, 2023)
Yunyang Wang,1 Jie Lu1- 3 1Department of Endocrinology and Metabolism, the Affiliated Hospital of Qingdao University, Qingdao, People's Republic of China; 2Shandong Provincial Key Laboratory of Metabolic Diseases and Qingdao Key Laboratory of Gout, the Affiliated Hospital of Qingdao University, Qingdao, People's Republic of China; 3Shandong Provincial Clinical Research Center for Immune Diseases and Gout, the Affiliated Hospital of Qingdao University, Qingdao, People's Republic of ChinaCorrespondence: Jie Lu, Shandong Provincial Key Laboratory of Metabolic Diseases and Qingdao Key Laboratory of Gout, the Affiliated Hospital of Qingdao University, 16 Jiangsu Road, Qingdao, Shandong, People's Republic of China, 266003, Tel +86 17853297395, Fax +86 0532-82912019, Email 13127006046@163.comAbstract: Serum urate (SU) is an independent predictor for the incidence of diabetes. In current diabetes treatment regimens, there is insufficient appreciation of the importance of hyperuricemia (HU) in disease control and prevention. To summarize the updated knowledge on the effects of SU on β-cell function, insulin resistance and chronic diabetic complications, as well as to evaluate the management of patients with both HU and diabetes, we searched the MEDLINE PubMed database, and included 285 journal articles. An inverted U-shaped relationship between fasting plasma glucose and SU levels was established in this review. Elevated SU levels may enhance the development of chronic diabetic complications, including macrovascular and microvascular dysfunction. Diet and exercise are essential parts of the lifestyle changes necessary for HU and diabetes management. Glucose- and urate-lowering drug selection and combination should be made with the principle of ameliorating, and at least not deteriorating, diabetes and HU. Medical artificial intelligence technology and monitoring systems can help to improve the effectiveness of long-term management of HU and diabetes through digital healthcare. This study comprehensively reviews and provides a scientific and reliable basis for and viewpoints on the clinical management of diabetes and HU.Keywords: diabetes, hyperuricemia, U-shaped relationship, urate-lowering treatment, management